Cultural adaptation of the Retirement Resources Inventory for Brazilian culture - Raquel Gvozd (Revista de Saúde Pública, 2019)
OBJECTIVE: To translate and adapt the Retirement Resources Inventory for Brazilian culture. METHODS: Methodological research including the stages of translation, synthesis, evaluation by committee of judges, back-translation and pre-test. The internal consistency of the instrument with Cronbach’s alpha coefficient was evaluated.RESULTS: We considered the stages of translation and cultural adaptation adequate. The evaluation of the synthesis version by the judges resulted in the need to change 95.0% of the items to ensure the semantic, idiomatic, cultural and conceptual equivalence between the original and translated versions. In general consensus of the instrument, the agreement rate among the judges for the equivalences was 84.4%. As for the pre-test stage, 25 pre-retirees participated. The participants suggested adjustments in the instrument. The instrument’s internal consistency was 0.85. The mean time to fill in the instrument was 18.7 minutes. CONCLUSIONS: The methodological process of cultural adaptation of the Retirement Resources Inventory resulted in adequate content validity and ease of understanding by the participants. We emphasize that this study precedes the evaluation process of the psychometric properties of the instrument, which will be carried out in new studies.